Risk factors and renal outcomes of AKI in children with secondary steroid-resistant nephrotic syndrome - Nannan Yu; XiaoJun Ouyang; Jie Li; Jie Gao; Shuhan Zeng; Hongjie Zhuang; Mengjie Jiang; Yuxin Pei; Xiaoyun Jiang (Renal Failure)
Background Acute kidney injury (AKI) is increasingly prevalent in children with nephrotic syndrome (NS). It is associated with adverse outcomes in NS, especially steroid-resistant nephrotic syndrome (SRNS). The incidence, risk factors and outcomes of AKI in secondary SRNS remain undefined. The main objectives of this study were to determine the risk factors and prognosis of AKI in hospitalized children with secondary SRNS.Material and methods This retrospective study was conducted from January 2014 to December 2019, involving 172 hospitalizations with secondary SRNS admitted to the First Affiliated Hospital of Sun Yat-sen University. AKI was defined and classified in accordance with the 2012 Kidney Disease Improving Global Outcomes (KDIGO) guidelines.Results AKI was found in 67 (39.0%) of 172 hospitalizations with secondary SRNS. Average age of onset in our group is 4.4 (3.1, 6.7) years with AKI and 3.7 (1.8, 5.6) years without AKI. Urea nitrogen level is 5.9 (4.1, 10.0) mmol/L with AKI and 5.1 (3.7, 7.0) mmol/L. Uric acid level is 446.0 (340.0, 567.0) umol/L with AKI and 401.0 (303.0, 496.0) umol/L. 24-h urinary protein level is 4.14 (2.9, 6.5) g with AKI and 2.5 (1.3, 5.3) without AKI. Multivariate logistic regression revealed that infection (OR = 5.287; 95% confidence interval, 2.349 to 11.899; p < 0.001), age at onset (OR = 1.180; 95% confidence interval, 1.032 to 1.349; p = 0.015) and uric acid level (OR = 1.003; 95% confidence interval, 1.000 to 1.006; p = 0.031) were significantly associated with the development of AKI in children with secondary SRNS. Among 72 children with secondary SRNS, six went to end-stage kidney disease (ESKD). Children in the AKI group were more likely to progress to ESKD compared with children in the non-AKI group (p = 0.017) with a median follow‐up of 48.5months.Conclusion AKI occurred in 39.0% of total hospitalizations associated with secondary SRNS. Risk factors including infection, age of onset, and uric acid level are associated with AKI in children with secondary SRNS. Furthermore, AKI was identified as a risk factor for the progression of secondary SRNS to ESKD.